1936
DOI: 10.1111/j.1746-1561.1936.tb08846.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of Normal and Pathological Locomotion in Man

Abstract: PIp. vi+48. 4 text-figs. and 15 plates. Price l0s. 6d. net. This book presents a full and ordered account of the method of dissection of the brain by defibrillation or blunt dissection, and some of the results to be obtained by this method are shown in the many illustrations, almost all of which are photographs of actual specimens.Though the method is not new and has been used in England previously by Jamieson and by Green, as far as we know it has not been set out in book form as a laboratory manual until now… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1937
1937
1978
1978

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Carlsoo (1972) and others (Farber, 1969, pp. 103-113;Napier, 1967;Steindler, 1935) provide an informative description of human gait. It is a modification of the Philippson step cycle used in the analysis of animal gait (see Grillner, 1975).…”
Section: Results Anddiscussionmentioning
confidence: 99%
“…Carlsoo (1972) and others (Farber, 1969, pp. 103-113;Napier, 1967;Steindler, 1935) provide an informative description of human gait. It is a modification of the Philippson step cycle used in the analysis of animal gait (see Grillner, 1975).…”
Section: Results Anddiscussionmentioning
confidence: 99%
“…Step Cycle Carlsoo (1972), among others (see Inman, 1966;Murray, 1967;Napier, 1967;Steindler, 1935), provided a useful description of human gait as a modification of the Philippson step cycle (see Grillner, 1975;Sukhanov, 1974). A stride begins when the body sways slightly forward placing the center of gravity in front of the feet.…”
Section: Thementioning
confidence: 99%
“…We assume that the same principles hold for each agonist/antagonist pair involved, and thus the discussion represents an average behavior of all pairs contributing to the actual limb motion. The human locomotor system is equipped with an abundance of two joint muscles; however, Steindler [4], Eberhart et al [ 10] have shown how two joint muscles can be functionally decomposed into the one joint variety, b. Derivation.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 40% is swing motion. The deploy (or restraint) portion in stance takes 10 to 1 5% of a double-step period [4,19].…”
Section: Quantitative Features Of the Biped Gaitmentioning
confidence: 99%
See 1 more Smart Citation